THE IMPACT OF GREEN ACCOUNTING IMPLEMENTATION AND AUDITOR REPUTATION ON COMPANY VALUE - Rosahayu Situmorang; Richard Friendly Simbolon; Mila Susanti (MESP–FEB UNS, 2026)
In emerging markets, green accounting and auditor reputation have emerged as important determinants of business value. However, the combined impact of the two remains understudied in Indonesia. This study argues that, based on agency and signaling theory, ESG disclosures and Big Four audit affiliation serve as additional signals that reduce information asymmetry between investors and companies. This quantitative study employed a causal research design. Purposive sampling was used to select a sample of 85 companies listed on the Indonesia Stock Exchange (IDX) in 2024. Firm value was calculated using Tobin's Q ratio, IDX ESG performance score indicating green accounting, and auditor reputation operationalized as a binary variable indicating Big Four affiliation. The hypothesized relationship was tested using multiple linear regression. The results showed that green accounting had a significant positive effect on firm value (β = 0.115; p < 0.001), and auditor reputation also had a significant positive effect (β = 6.982; p < 0.001). However, these figures collectively account for a significant portion of the variation in firm value (F = 487.023; p < 0.001; R2 = 0.904), although consideration of sample pre-selection and mode specification should be considered. According to these findings, transparent environmental reporting enhances corporate accountability, and Big Four affiliation enhances investor confidence in financial reporting. This study suggests that audit diversity and credibility jointly enhance market valuation, with practical implications for corporate reporting strategies and investor decision-making in emerging markets. This adds to the emerging market ESG literature.